1994
DOI: 10.1111/j.1476-5381.1994.tb17089.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of the ATP‐mediated increase in L‐type calcium current amplitude and activation of a non‐specific cationic current in rat ventricular cells

Abstract: 1 The pharmacological profile of the ATP-induced increase in Ica amplitude and of ATP activation of a non-specific cationic current, IATp, was investigated in rat ventricular cells.2 The EC50 values for Ic, increase and IATp activation were 0.36 pM and 0.76 FtM respectively. Suramin (1O tM) and cibacron blue (1 gM) competitively antagonized both effects of ATP. 3 The rank order of efficacy and potency of ATP analogues in increasing IC, amplitude was 2-methylthio-ATP ftATPtATPyS. The derivatives j-methylene-ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
2
37
2
Order By: Relevance
“…3). Moreover, ATP-dependent calcium influx was reportedly blocked by suramin (19), whereas the effect of the nucleotide on glucose transport was not influenced by this antagonist (Fig. 2).…”
Section: Discussionmentioning
confidence: 84%
“…3). Moreover, ATP-dependent calcium influx was reportedly blocked by suramin (19), whereas the effect of the nucleotide on glucose transport was not influenced by this antagonist (Fig. 2).…”
Section: Discussionmentioning
confidence: 84%
“…Using a train protocol to measure the rate of block of the Ltype Ca21 channel current (Kass & Arena, 1989) previously reported on atrial and ventricular preparations in the literature (which occurred within several minutes instead of seconds) (Alvarez et al, 1990;Qu et al, 1993 washout on the sinus node activity has been reported in only one study on the isolated, spontaneously beating guinea-pig heart preparation (Stark et al, 1993), whereas in other reported studies the [ATP]O-induced effect disappeared gradually (3-5 min) following washout (Alvarez et al, 1990;Scamps et al, 1992;Qu et al, 1993;Scamps & Vassort, 1994 (Scamps et al, 1992;Qu et al, 1993). In order to investigate the type(s) of purinoceptor involved in our present study, different commercially available purinoceptor antagonists were examined.…”
Section: Discussionmentioning
confidence: 91%
“…Most studies in the literature examining the modulatory effects of [ATP]o on L-type Ca2+ channel currents have used myocytes isolated from atria and ventricles (Alvarez et al, 1990;Qu et al, 1992;Mantelli et al, 1993;Scamps et al, 1992;Scamps & Vassort, 1994) and both an increase and a decrease in the L-type Ca21 channel current amplitude, has been reported. Unlike the atrial and ventricular myocardia, in the SAN the L-type Ca2+ channel current has been suggested to play an important role in the initiation of the action potential (Irisawa & Noma, 1984, Doerr et al, 1989 1 Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…For adult skeletal muscle, ATP has been found to facilitate acetylcholine stimulation via an unidentified second messenger pathway (21) and in rat diaphragm ATP␥S increases inositol phosphate formation (22). For cardiac myocytes, while some ATP-induced cationic currents seen there may be due to P2X purinoceptors, the positive inotropic effects of ATP and its potent ability to increase calcium transients in stimulated rat heart and to increase the L-type calcium current in cardiac myocytes have been attributed to metabotropic (P2Y) purinoceptors (23)(24)(25)(26). ATP was found to be active on ventricular myocytes with EC 50 ϳ300 nM and 2-MeSATP and ATP␥S were similarly highly potent (24).…”
Section: Analysis Of the P2ymentioning
confidence: 99%